Solar energy technical feasibility comparison: an alternative proposal for the Industry - Gurturk, Mert; Erdem, Murat; Ucar, Ferhat (Springer, 2024)
In this study, 11 provinces with more than 1 MW solar power plants (SPP) in Turkey have been examined in terms of global solar radiation and power produced. The main objective of this study is to underline the serious differences in technical feasibility analysis conducted by the academic circles and solar energy industrial environments in Turkey. The obtained results were compared with the values operated by the private installation companies in the industry, these were interpreted, and the disagreements were revealed. Moreover, the study reveals some gaps in technical feasibility analysis, which the sector professionals usually ignore in the field. The findings were evaluated in monthly, annual, and seasonal time zones. The present study showed that the analysis, to which private companies in the field refer, is insufficient and the parameters that would guide the investor in detail could not be obtained. More detailed prospection has been obtained within the scope of this study.Considering the whole of our findings, while the most advantageous location for investing in SPPs in Antalya with a total of 97.50 h monthly average sunshine duration and radiation of 59,599.6 W/m2 throughout the year, the most disadvantaged location is Kahramanmara & scedil; with a total monthly average sunshine duration of 80.80 h and a radiation value of 44,810.8 W/m2-year. Antalya is followed by Mardin location (monthly average sunshine duration of 96.10 h and radiation of 59,487.9 W/m2-year) and Karaman (monthly average sunshine duration of 94.40 h and radiation of 58,847.1 W/m2-year).
Keywords: Energy; Solar energy; Radiation; Solar power plant; Technical feasibility